Negative Reflections of Ottomans and Persian struyy on Iraq (1508 - 1914) - غزوة سعيد عبود (College of Education for Women, 2019)
Continuous conflict between Parisian and Ottoman states the results that Iraq became as aground for their battles which leads to their own interests in Iraq which are shape their strategy. The conflict continues for long time. In spite of, they signed many treatments and protocols between the two sides, as Arzarom treaty , the first and the second, Tahran protocols , and Astana protocol. This conflict, no sides of them to dose any part of their land, but these treaties leaded to a big loss to Iraq ,which lost parts of it's land and water area in Ahwaz and shatt AL-Arab, so, Iraq became as a smoth target for their interests, and lost its sovereignty,and lost self-govern of the country country . so the research concludes the following.